2005
DOI: 10.1086/427510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tumor Necrosis Factor–α–Related Apoptosis‐Inducing Ligand and Its Proapoptotic Receptors Is Down‐Regulated during Gastric Infection with VirulentcagA+/vacAs1+Helicobacter pyloriStrains

Abstract: Down-regulation of the TRAIL system, in the context of H. pylori infection, may limit exaggerated apoptosis of gastric epithelial cells and destruction of tissue and, therefore, may enable H. pylori to maintain its niche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…One model of H. pylori -induced gastric carcinogenesis proposes that apoptosis of mucosal cells leads to a compensatory epithelial cell proliferation [6,7]. So far, the mechanisms T-cell apoptosis induced by H. pylori are not fully understood [10]. The loss of immunocompetent, cells due to H. pylori -induced apoptosis could explain the impaired or inappropriate host T-cell response in the gastric mucosa towards H. pylori .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One model of H. pylori -induced gastric carcinogenesis proposes that apoptosis of mucosal cells leads to a compensatory epithelial cell proliferation [6,7]. So far, the mechanisms T-cell apoptosis induced by H. pylori are not fully understood [10]. The loss of immunocompetent, cells due to H. pylori -induced apoptosis could explain the impaired or inappropriate host T-cell response in the gastric mucosa towards H. pylori .…”
Section: Introductionmentioning
confidence: 99%
“…The loss of immunocompetent, cells due to H. pylori -induced apoptosis could explain the impaired or inappropriate host T-cell response in the gastric mucosa towards H. pylori . So far, the mechanisms T-cell apoptosis induced by H. pylori are not fully understood [10]. Moreover, it is still unclear how H. pylori , despite inducing a local and systemic immune response, can evade the immune system [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interplay between bacterial factors and host signal transduction pathways determine host cell apoptotic or antiapoptotic events 4, 5 . H. pylori -mediated apoptosis involves activation of MHC class II,6 p53,7 Fas/FasL system,8 and TNF-related apoptosis inducing ligand (TRAIL) 9 . H. pylori enhance Bax expression10 and mitochondrial translocation leading to GEC death 11.…”
mentioning
confidence: 99%
“…For example, it has been shown that infection of the gastric mucosa with H. pylori leads to increased apoptosis of the gastric epithelial cells, which enhances antigen survival (Neu et al, 2005). The cytotoxin associated gene A (cagA) is a particular strain of H. pylori thought by some researchers to be particularly virulent and proinflammatory.…”
Section: Geneticsmentioning
confidence: 99%